マウスの社会ストレスはミクログリアとシナプスとの接触を誘発し、シナプスのプロテオグリカンからのヘパラン硫酸の放出に寄与する - 永井, 碧; 大野, 伸彦; 灘中, 里美; 沼, 知里; 北川, 裕之; 永井, 裕崇; 古屋敷, 智之; 川島, 祐介 (日本薬理学会年会要旨集, 2023)
Chronic stress due to aversive and demanding conditions induces dendritic atrophy and synaptic loss of pyramidal neurons in the medial prefrontal cortex (mPFC), leading to depression-related behaviors. Chronic stress reportedly activates microglia via the innate immune receptors TLR2/4, leading to dendritic atrophy and synaptic loss of mPFC neurons and depression-related behaviors in mice. Here, we examined the mechanistic link between microglial activation and neuronal dysfunctions under social defeat stress in mice. Serial electron microscopy showed that social stress transiently increased the interaction between microglial processes and synapses, preferentially presynaptic sites. Proteoglycans reportedly include putative TLR2/4 ligands and are involved in synaptic development and functions. Carbohydrate LC-MS analysis showed that social stress specifically decreased heparan sulfate, known to be a TLR4 ligand, in synaptosomes but not in the whole mPFC tissue. This heparan sulfate decrease was abolished in TLR2/4 knockout mice, which lack stress-induced microglial activation. These findings suggest that social stress induces microglial contact with synapses, where TLR2/4 contributes to the release of heparan sulfate from synaptic proteoglycans, perhaps to activate microglia.